Shear banding stability and fracture of metallic glass: Effect of external confinement. (May 2020) - Qu, R.T.; Wu, S.J.; Wang, S.G.; Wang, X.D.; Zhang, Z.F.
Highlights: The effect of confinement on the plastic deformation of MG was systematically studied. The external confinement can significantly improve the stability of shear banding. The kinetic and energy dissipation equations for the confined MG were derived. The mechanisms of confinement effect in various confined MG systems were summarized. Abstract: While metallic glasses (MGs) usually fracture catastrophically under uniaxial loading, external confinement like coating has been proved quite effective for improving the plasticity. The positive effect of confinement was mainly attributed to the lateral confining stress on the interface between sample and confinement, which impedes the excess propagation of shear bands and promotes their multiplication. Here we show that, even though there is no contact between the MG and the confinement, the brittle fracture can be effectively suppressed. Three dimensional (3D) high resolution X-ray tomography observations successfully captured the shear-band cracking evolution and confirmed that the external confinement caused the change of shear-band fracture mode. Analysis on the thermodynamics and kinetics of shear banding in the confined MG shows that the confinement extremely reduces the shear velocity, contributes to the shear band arrest, and largely lowers the energy release rate, leading to the increase of the shear stability and the resistance to instant fracture. Finally, the mechanisms of confinement effect on the plastic deformation in various confined MG systems were summarized. These results suggest new understandings on the effect of confinement for the fracture of MG composites or coated MG structures, and on the mechanisms of shear-band cracking and fracture in different MG loading systems.